THE IMPORTANCE OF TRANSLATING SOCIOLINGUISTIC UNITS IN LITERARY TRANSLATION - Ulug‘Bek Ravshanbekovich Yo‘Ldoshev; Nilufar Najmiddinova (Western European Studies, 2025)
The process of literary translation requires not only linguistic competence but also a deep understanding of the sociolinguistic aspects embedded in the source language. Sociolinguistic units, such as dialects, sociolects, and cultural references, play a significant role in shaping the authenticity and context of the original text. Their correct translation ensures that the essence, tone, and cultural nuances are preserved. This paper explores the significance of translating sociolinguistic units in literary texts and highlights the challenges faced by translators in maintaining the integrity of the source material while adapting it for a target audience. The study focuses on strategies for handling these units and suggests practical solutions for overcoming difficulties in the translation process
Keywords: Literary Translation; Sociolinguistic Units; Dialects